INTEGRITY, UNETHICAL BEHAVIOR, AND TENDENCY OF FRAUD - Gugus Irianto; Nurlita Novianti; Kristin Rosalina; Yuki Firmanto (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2012)
The purpose of this research is to analyze the influence of integrity, and compensation systems on unethical behavior, and the influence of unethical behavior on tendency of fraud. The sample used in this research is the staff of financial, and procurement divisions of a higher educational institution. The result of the research indicates that integrity has no influence on unethical behavior, whilst compensation systems have an influence on unethical behavior. The other result shows that ethical environment could drive decision based on ethical principles rather than personal interest. In other words, the tendency of fraud may be reduced by the existence of ethical environment. The results of the study may be further interpreted that appropriate system, integrity, and ethical environment are determinant to ethical behavior.